(30x + 15) / x divided by (10 / 3x)
First, simplify the expression within the first set of parentheses:
(30x + 15) / x = 15(2x + 1) / x = 15(2 + 1/x) = 30 + 15/x
Divide this by the expression in the second set of parentheses:
(30 + 15/x) / (10 / 3x) = (30 + 15/x) * (3x / 10) = 90x / 10 + 45x / 10 = 9x + 4.5x = 13.5x
So, the final simplified answer is 13.5x.
divide and simplify
30x+15/x divided by 10/3x
3 answers
invert the second fraction and multiply normally
(30x + 15) / x * (3x / 10)
First, we will invert the second fraction:
(30x + 15) / x * (3x / 10) = (30x + 15) / x * (3x / 10) = (30x + 15) / x * (3x / 10)
Now, multiply the numerators and denominators:
(30x * 3x + 15 * 3x) / (x * 10) = (90x^2 + 45x) / 10 = 9x(10x + 5) / 10 = 9x(2x + 1) = 18x^2 + 9x
So, the final multiplication after inverting the second fraction is 18x^2 + 9x.
First, we will invert the second fraction:
(30x + 15) / x * (3x / 10) = (30x + 15) / x * (3x / 10) = (30x + 15) / x * (3x / 10)
Now, multiply the numerators and denominators:
(30x * 3x + 15 * 3x) / (x * 10) = (90x^2 + 45x) / 10 = 9x(10x + 5) / 10 = 9x(2x + 1) = 18x^2 + 9x
So, the final multiplication after inverting the second fraction is 18x^2 + 9x.